Latent M. tuberculosis infection is associated with increased inflammatory cytokine and decreased suppressor of cytokine signalling (SOCS)‐3 in the diabetic host. (30th December 2021) - Masood, Kiran Iqbal; Irfan, Muhammad; Masood, Qamar; Yameen, Maliha; Jamil, Bushra; Ram, Nanik; Rao, Shoaib; Rottenberg, Martin; Hasan, Zahra
Abstract: Tuberculosis (TB) outcomes are worsened by type II diabetes mellitus (DM). Protective immunity against Mycobacterium tuberculosis (MTB) is driven by cytokines. Latent TB (LTBi) is common but its effect on the diabetic host is not well understood. We investigated mycobacterial antigen‐stimulated responses in peripheral blood mononuclear cell (PBMC) isolated from healthy endemic controls (EC), those with LTBi, DM groups with and without LTBi, as compared with TB patients. Cytokines were measured using a Luminex‐based assay. Gene expression was determined by RT‐PCR. In DM‐LTBi cases, PPD‐stimulated proinflammatory cytokines; IFN‐γ, IL‐6, IL‐2, TNF‐α and GM‐CSF and anti‐inflammatory cytokines, IL‐5 and IL‐13 were raised as compared with EC. DM‐LTBi PPD‐stimulated IFN‐γ, IL‐6 and TNF‐α mRNA titres were found raised in DM‐LTBi, whilst suppressor of cytokine signalling (SOCS)‐3 expression was lowered. Within DM cases, stratification based on HbA1c levels revealed raised IFN‐γ but lowered IL‐6 gene expression in those with controlled levels as compared with uncontrolled glycaemic levels. Further, SOCS1 expression levels were found higher in DM cases with controlled glycaemia when compared with EC. Overall, we show that diabetics with LTBi manifest raised levels of inflammatory and anti‐inflammatory cytokines concomitant with reduced SOCS3 mRNA expression. Reduced glycaemic control results in further inflammatory dysregulation impacting conversing impacting IFN‐γ and IL‐6 activation. These results suggest that dysregulated immune activation in diabetes is exacerbated by LTBi, lack of glycaemic control may further compromise immunity against MTB infection.